L’Italia compie 150 anni. E gli italiani? Una riflessione sul senso di appartenenza, sull’identità e sull’insuperata asimmetria tra Italia e italiani - Giumelli, Riccardo (SocietàMutamentoPolitica, 2011)
If Italy in 2011 becomes 150 years old, than how old are Italians? So to paraphrase the title of this paper, we introduce mischievously the idea that Italians have a different age. Obviously, we will try to respond, reflecting on the sense of belonging to a collective identity, in our case the Italian one, in times of globalization or, better, glocalization. The reflexion about Italian identity, or Italic as we are going to call it, comes from the extraordinary and special change due to the global processes that deconstruct the socio-political systems of nation-state created by the Treaty of Westphalia in 1648, which ended the Thirty Years' War. In conclusion, what interests us is the cultural identity is increasingly characterized by processes of human, objects and symbols mobility that no longer recognize, as they did for a long time, territorial barriers and boundaries.